Recruitment and communication of food source location in three species of stingless bees (Hymenoptera, Apidae, Meliponini) - Aguilar Ingrid (2005)
This study reports on controlled experiments of the recruitment behavior and location communication in three species of stingless bee Trigona corvina, Plebeia tica and Trigona (Tetragonisca) angustula. We trained bees to a sugar water feeder at 50 m and placed identical control feeders either at different distances or in different directions with respect to the nest. Both the distance and direction of the food source were communicated very accurately in T. corvina. In P. tica and T. angustula the direction of the food source was communicated. In the distance experiments with P. tica, newcomers arrived mostly at the food source nearest to the nest. Only when the control feeder had a different odor than the experimental feeder did most recruits find the experimental feeder. We found that experienced foragers of T. corvina and P. tica guide recruits to the food source by means of pilot flights. We discuss the potential mechanisms that these species may use for location communication and the implications of these differences for resource partitioning.